miR-181a negatively modulates synaptic plasticity in hippocampal cultures and its inhibition rescues memory deficits in a mouse model of Alzheimer's disease. - Rodriguez-Ortiz, Carlos; Prieto, Gilberto Aleph; Martini, Alessandra; Forner, Stefania; Trujillo-Estrada, Laura Isabel; LaFerla, Frank M.; Baglietto-Vargas, David; Cotman, Carl; Kitazawa, Masashi (Wiley, 2020)
MicroRNAs play a pivotal role in rapid, dynamic, and spatiotemporal modulation ofsynaptic functions. Among them, recent emerging evidence highlights that micro-RNA-181a (miR-181a) is particularly abundant in hippocampal neurons and controlsthe expression of key plasticity-related proteins at synapses. We have previouslydemonstrated that miR-181a was upregulated in the hippocampus of a mouse modelof Alzheimer's disease (AD) and correlated with reduced levels of plasticity-relatedproteins. Here, we further investigated the underlying mechanisms by which miR-181a negatively modulated synaptic plasticity and memory. In primary hippocampalcultures, we found that an activity-dependent upregulation of the microRNA-regu-lating protein, translin, correlated with reduction of miR-181a upon chemical long-term potentiation (cLTP), which induced upregulation of GluA2, a predicted target formiR-181a, and other plasticity-related proteins. Additionally, Aβ treatment inhibitedcLTP-dependent induction of translin and subsequent reduction of miR-181a, andcotreatment with miR-181a antagomir effectively reversed the effects elicited by Aβbut did not rescue translin levels, suggesting that the activity-dependent upregula-tion of translin was upstream of miR-181a. In mice, a learning episode markedly de-creased miR-181a in the hippocampus and raised the protein levels of GluA2. Lastly,we observed that inhibition of miR-181a alleviated memory deficits and increasedGluA2 and GluA1 levels, without restoring translin, in the 3xTg-AD model. Taken to-gether, our results indicate that miR-181a is a major negative regulator of the cellularevents that underlie synaptic plasticity and memory through AMPA receptors, andimportantly, Aβ disrupts this process by suppressing translin and leads to synapticdysfunction and memory impairments in AD.
Keywords: Alzheimer, Enfermedad de; Memoria; Hipocampo (Cerebro); Neuroplasticidad; AMPA receptor; Amyloid-beta oligomers; GluA2; Long-term potentiation; MicroRNAs; Spatial memory; Translin/trax